1993
DOI: 10.1111/j.1365-2621.1993.tb06190.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass Production Method for Rice Protein Isolate and Nutritional Evaluation

Abstract: Production of RPIWe developed a method for mass production of rice protein isolate (RPI) and evaluated its nutritional quality in rats. To obtain thick slurry, rice flour was mixed with a 0.6% Termamyl 12OL-solution (1:2, w/v) at room temperature (-23°C). The slurry was heated at 97°C for 2 hr with stirring. Gelatinization and liquefaction occurred simultaneously. RPI obtained by filtration and washing with boiling water, was more than 90% pure protein (dry matter basis). It also contained 6.4% dietary fiber, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 26 publications
(8 reference statements)
1
50
0
3
Order By: Relevance
“…Sin embargo, tanto la harina como la FRP exhibieron estar limitadas por los aminoa´cidos lisina y triptofano, siendo el ma´s significativo el segundo, que mostro´un valor de 9,5 g/kg de proteı´na en la harina y de 8,0 g/kg de proteı´na, en comparacio´n con el esta´ndar de FAO, que es de 11 g/kg de proteı´na. Dicho valor puede ser considerado aceptable si se compara con los resultado obtenidos para proteı´nas tanto de harina como de aislado de lupino donde se reporta un valor de 6 g/kg de proteı´na para ambas muestras (Lqari, Vioque, Pedroche, & Milla´n, 2002) asıć omo para proteı´nas del salvado de arroz (7 g/kg de proteı´na), pero resulto´inferior al reportado para el aislado proteı´nico del mismo salvado de 12 g/kg de proteı´na (Wang, Hettiarachchy, Burks, & Siebenmorgen, 1999) y otras fuentes usadas de forma convencional, como aislado proteı´nico de soya con 12 g/kg de proteı´na y caseı´na con 14 g/kg de proteı´na (Morita & Kiriyama, 1993).…”
Section: Determinacio´n De Aminoa´cidosunclassified
“…Sin embargo, tanto la harina como la FRP exhibieron estar limitadas por los aminoa´cidos lisina y triptofano, siendo el ma´s significativo el segundo, que mostro´un valor de 9,5 g/kg de proteı´na en la harina y de 8,0 g/kg de proteı´na, en comparacio´n con el esta´ndar de FAO, que es de 11 g/kg de proteı´na. Dicho valor puede ser considerado aceptable si se compara con los resultado obtenidos para proteı´nas tanto de harina como de aislado de lupino donde se reporta un valor de 6 g/kg de proteı´na para ambas muestras (Lqari, Vioque, Pedroche, & Milla´n, 2002) asıć omo para proteı´nas del salvado de arroz (7 g/kg de proteı´na), pero resulto´inferior al reportado para el aislado proteı´nico del mismo salvado de 12 g/kg de proteı´na (Wang, Hettiarachchy, Burks, & Siebenmorgen, 1999) y otras fuentes usadas de forma convencional, como aislado proteı´nico de soya con 12 g/kg de proteı´na y caseı´na con 14 g/kg de proteı´na (Morita & Kiriyama, 1993).…”
Section: Determinacio´n De Aminoa´cidosunclassified
“…22,23) Both proteins were prepared by the alkaline extraction method (Shimada, Inc., Nagaoka, Japan). 11,19) Casein (CAS) and soy protein isolates (SPI) were obtained from Fontera (Kanagawa, Japan), and Fuji Oil Co. (Osaka, Japan), respectively. The chemical composition of these dietary proteins was analyzed, and it is shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Yoshida et al reported that the serum and liver levels of total cholesterol and total lipids in rats fed 15% rice protein was close to that of a casein group, indicating that rice protein is not likely to have a hypocholesterolemic effect like soy protein, even though it increased fecal bile acid excretion as compared with casein. 8,9) But, Sugano et al 10) and Morita et al 11,12) found that rice protein exerted a cholesterol-lowering effect on serum and liver levels, with higher fecal excretion at more than 20% protein levels. This hypocholesterolemic effect of rice protein was confirmed by Tran and Nicolosi in hamsters, indicating that rice protein lowered plasma total cholesterol and reduced early atherosclerosis as efficaciously as soy protein.…”
mentioning
confidence: 99%
“…It is a major source of energy and protein, and has been getting increasing attention as a healthy, nutritious, and hypoallergenic foodstuff, 1,2) reportedly including hypocholesterolemic and hypolipidemic effects comparable to soy protein. [3][4][5] The proteins in rice endosperm include glutelin, prolamin, globulin, albumin, etc. Two major proteins, glutelin and prolamin, are storage proteins.…”
Section: Improvement In the In Vivo Digestibility Of Rice Protein By mentioning
confidence: 99%